Sport und Studienerfolg Analysen zur Bedeutung sportlicher Aktivität im Setting Hochschule - Göring, Arne (Universitätsverlag Göttingen, 2020)
In recent years, the topic of "academic success" has gained enormous importance in both higher education policy and the sciences. The 4th volume of the series 'University Sports: Education and Science' takes up this development from a sports science perspective and examines possible connections between sporting activity and academic success with an interdisciplinary focus. In order to record and expand the scientific knowledge on the relevance of sporting activity in the university setting, scientists from various disciplines present their thoughts, observations and findings on the topic. Based on a broad understanding of the concept of academic success, the significance of sporting activity is analyzed in terms of institutional criteria (e.g. final grade, length of study or dropout) as well as individual factors (e.g. study satisfaction, health skills, social skills, psychosocial health).